2022
DOI: 10.3390/cells11213338
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stem Cells (ADSCs) Supplemented with Hepatocyte Growth Factor (HGF) Attenuate Hepatic Stellate Cell Activation and Liver Fibrosis by Inhibiting the TGF-β/Smad Signaling Pathway in Chemical-Induced Liver Fibrosis Associated with Diabetes

Abstract: Liver fibrosis can develop on the background of hyperglycemia in diabetes mellitus. However, xenobiotic-related factors may accelerate diabetes-associated liver fibrosis. In this study, we aimed to assess the antfibrotic effect of ADSC and HGF therapy and to establish the cellular and molecular mechanisms through in vitro and in vivo experiments. In vitro, TGF-β1-activated hepatic stellate cells (HSCs) were cocultured with ADSCs or HGF, and the expression of several fibrosis markers was investigated. The antif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…However, studies have shown that under continuous high glucose environments, the glucose metabolism, cell replication, apoptosis, and differentiation ability of ADSCs are impaired, with a more pronounced negative impact on ADSCs derived from patients with diabetes[38] Liver tissue can be damaged in the hyperglycemic environment of diabetes, leading to liver brosis. Addition of hepatocyte growth factors to ADSCs has been proposed as a method to treat liver brosis in diabetic patients [39]. Our study showed differences in the biological functions of AML-12 cells between sEV A and sEV AG .…”
Section: Discussionmentioning
confidence: 62%
“…However, studies have shown that under continuous high glucose environments, the glucose metabolism, cell replication, apoptosis, and differentiation ability of ADSCs are impaired, with a more pronounced negative impact on ADSCs derived from patients with diabetes[38] Liver tissue can be damaged in the hyperglycemic environment of diabetes, leading to liver brosis. Addition of hepatocyte growth factors to ADSCs has been proposed as a method to treat liver brosis in diabetic patients [39]. Our study showed differences in the biological functions of AML-12 cells between sEV A and sEV AG .…”
Section: Discussionmentioning
confidence: 62%
“…Liver tissue can be damaged in the hyperglycemic environment of diabetes, leading to liver fibrosis. Addition of hepatocyte growth factors to ADSCs has been proposed as a method to treat liver fibrosis in diabetic patients [ 47 ]. Our study showed differences in the biological functions of AML-12 cells between sEV A and sEV AG .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that vascular endothelial growth factor (VEGF) is an active regulator of brain-derived neurotrophic factor (BDNF) production in diabetic patients after extraction of primary retinal Müller cells [ 21 ]. Sami [ 22 ] demonstrated that hepatocyte growth factor (HGF)-based ADSC therapy may be useful in the treatment of liver fibrosis in diabetic patients. Thus, the primary cell co-culture model was used as a whole model to simulate the body tissue or organ, and the stress response of macrophages was studied under the condition of adipose tissue obesity.…”
Section: Discussionmentioning
confidence: 99%